2019
DOI: 10.1021/acs.jafc.9b06155
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Cyanidin-3-arabinoside Extracted from Blueberry as a Selective Protein Tyrosine Phosphatase 1B Inhibitor

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is an important target for type 2 diabetes. PTP1B inhibitors can reduce blood glucose levels by increasing insulin sensitivity. Anthocyanins often play a hypoglycemic effect, but the research about them have mainly focused on glucosidase. At present, the research about protein tyrosine phosphatase 1B (PTP1B) target is less, and the corresponding molecular mechanism is still unclear. Therefore, in this present study, anthocyanins isolated from blueberry were used to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 30 publications
7
44
0
Order By: Relevance
“…Protein tyrosine phosphatase 1B (PTP1B) is another promising pharmacological target for the treatment of T2DM as it can reduce blood glucose levels by increasing insulin sensitivity [ 100 ]. Notably, Tian et al [ 101 ] identified anthocyanins isolated from BB as selective inhibitors of PTP1B able to increase glucose consumption on HepG2 (human hepatoma) cells in a dose-dependent manner. Moreover, Nachar et al [ 102 ] performed an in vitro study with phenolic compounds from BB juice fermented with Serratia vaccinii and observed a strong antidiabetic potential in the liver and skeletal muscle, as it was able to regulate key enzymes involved in glycogen synthesis, gluconeogenesis and skeletal muscle glucose uptake.…”
Section: Blueberries Beneficial Outcomes In (Pre)diabetes Progression—a Multi-modal Functional Fruitmentioning
confidence: 99%
“…Protein tyrosine phosphatase 1B (PTP1B) is another promising pharmacological target for the treatment of T2DM as it can reduce blood glucose levels by increasing insulin sensitivity [ 100 ]. Notably, Tian et al [ 101 ] identified anthocyanins isolated from BB as selective inhibitors of PTP1B able to increase glucose consumption on HepG2 (human hepatoma) cells in a dose-dependent manner. Moreover, Nachar et al [ 102 ] performed an in vitro study with phenolic compounds from BB juice fermented with Serratia vaccinii and observed a strong antidiabetic potential in the liver and skeletal muscle, as it was able to regulate key enzymes involved in glycogen synthesis, gluconeogenesis and skeletal muscle glucose uptake.…”
Section: Blueberries Beneficial Outcomes In (Pre)diabetes Progression—a Multi-modal Functional Fruitmentioning
confidence: 99%
“…The PTP1B Inhibition assay was performed in 96-well plates [25]. The compound (10 µL) was added to the 99-µL reaction buffer solution, which consisted of 10 mM Tris (pH 7.4), 50 mM NaCl, 2 mM dithiothreitol (DTT), 1 mM MnCl 2 , and 10 mM para-nitrophenyl phosphate (pNPP).…”
Section: Ptp1b Inhibition Assaysmentioning
confidence: 99%
“…The PTP1B inhibition assay was performed in 96-well plates [18]. The compound (10 µL) was added to the 99 µL reaction buffer solution, which consisted of 10 mM Tris (pH 7.4), 50 mM NaCl, 2 mM dithiothreitol (DTT), 1 mM MnCl 2 , and 10 mM para-nitrophenyl phosphate (pNPP).…”
Section: Ptp1b Inhibition Assaysmentioning
confidence: 99%